Unlocking the potential: challenges and factors influencing the use of ICTs by smallholder maize farmers in Zimbabwe - Stella Nyakudya; Newettie Jambo; Pamela Madududu; Timothy Manyise (Cogent Economics & Finance, 2024)
The study aims to investigate the challenges faced by smallholder maize farmers and identify the pivotal factors influencing the adoption of ICTs in agriculture. A blend of descriptive and probit regression analytical techniques is applied by analyzing cross-sectional survey data from a selected multistage random sample of 155 maize farmers in Marondera Rural District, Zimbabwe. The study findings revealed that the foremost obstacles hampering ICT adoption include electricity shortages attributable to load-shedding and persistent communication network challenges. Additionally, it was observed that the utilization of mobile phones for agricultural purposes remains moderately low, while the use of computers in agriculture is strikingly minimal. The probit regression model results revealed that age, gender, access to credit, and extension contact are significant determinants for computer use in agriculture. Furthermore, critical influencers of mobile phone adoption for agricultural activities that were identified include farming experience, engagement in non-farm activities, credit access, remittances, and extension visits. The study recommends fostering an enabling environment to encourage farmers to embrace ICTs for agricultural purposes. To support this endeavor, the study advocates an improved agricultural training and extension system, with particular attention to less experienced and elderly farmers who may exhibit resistance to technological advancements.
Keywords: O10; Q16; Q28; 330; Smallholder farmers; probitregression model; challenges; ICTs; Zimbabwe